2009
DOI: 10.1128/jvi.01905-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Hepatitis B Virus in Peripheral Blood Leukocytes: Evidence for Selection and Compartmentalization of Viral Variants with the Immune Escape G145R Mutation

Abstract: The compartmentalization of viral variants in distinct host tissues is a frequent event in many viral infections. Although hepatitis B virus (HBV) classically is considered hepatotropic, it has strong lymphotropic properties as well. However, unlike other viruses, molecular evolutionary studies to characterize HBV variants in compartments other than hepatocytes or sera have not been performed. The present work attempted to characterize HBV sequences from the peripheral blood leukocytes (PBL) of a large set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 59 publications
4
49
1
1
Order By: Relevance
“…Furthermore, a recent report indicated that HBV strains vary in distinct compartments of chronically infected patients, revealing that immune escape sG145R mutants are frequently selected in peripheral blood leukocytes and may then serve as a source of reactivation or transmission (7). It is therefore important to understand the functional implications of immune escape mutations on the replication of HBV strains, especially on strains with common treatment-associated mutations, such as LAM resistance or HBeAg negativity (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent report indicated that HBV strains vary in distinct compartments of chronically infected patients, revealing that immune escape sG145R mutants are frequently selected in peripheral blood leukocytes and may then serve as a source of reactivation or transmission (7). It is therefore important to understand the functional implications of immune escape mutations on the replication of HBV strains, especially on strains with common treatment-associated mutations, such as LAM resistance or HBeAg negativity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Several conditions have been recognized in which HBV escape mutants arise in clinical practice: (i) treatment with anti-HBs immunoglobulin, e.g., after liver transplantation to avoid reinfection of the graft (23,32); (ii) antiviral therapy by itself, as the reading frames of the envelope and polymerase genes overlap and several resistance mutations in the polymerase selected during antiviral therapy simultaneously alter the antigenicity of HBsAg (20,21,31); and (iii) de novo infection of vaccinated individuals with escape mutants (19). Moreover, Datta et al recently reported that HBV variants with the sG145R immune escape mutation may very frequently "hide" in the peripheral blood leukocyte compartment of infected individuals (7).…”
mentioning
confidence: 99%
“…It is well known that HBV is lymphotropic as well as hepatotropic. Previous studies reported that G145R mutant was frequently detected in peripheral blood leukocytes from HBsAg-positive and negative patients [39, 40]. Moreover, HBV persisting lymphatic cells contribute to occult HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…To identify HBV genotypes, 10 samples, selected randomly from our population group, were analyzed using a nested polymerase chain reaction (PCR) that was sensitive for the genotyping of integrated HBV in the DNA of leukocytes (Datta et al, 2009). The amplified region contains a sufficient number of sites that vary between the different HBV strains to identify the viral subtype (A-H) using sequencing methods.…”
Section: Hbv Genotypingmentioning
confidence: 99%